Pengembangan Lembar Kerja Peserta Didik (LKPD) Matematika Dengan Pendekatan Saintifik Untuk Sekolah Menengah Kejuruan (SMK) Negeri 2 Kota Bengkulu - Afrya Wida Safitri; Andang Sunarto; Poni Saltifa (JPT : Jurnal Pendidikan Tematik, 2023)
This study aims to produce Mathematics Student Worksheets (LKPD) with a Scientific Approach for State Vocational High School (SMK) 2 Bengkulu City on the material of quadratic equations and functions that are valid, practical and effective. The type of research used is development research (Research and Development) with the Borg and Gall Sugiyono model. Based on the results of the product assessment from the material expert validator, the average result was 89.03% of the "Very Valid" criteria, and the results of the product assessment from the media expert validator, the average result was 91.70% of the "Very Valid" criteria. On the teacher's practicality questionnaire sheet, the results were 92.11% of the "Very Practical" criteria, and on the 27 students' practicality questionnaire sheet, the results were 87.58% of the "Very Practical" criteria. While the results of the student learning test obtained an N-Gain value for the experimental class obtained an average value of 0.81 "High" criteria and for the N-Gain value of the control class obtained an average value of 0.63 "Medium" criteria, the t-test value obtained was 0.000 while the level ???? = 0.05. Based on the results of the hypothesis test with the independent samples test, it was stated that the research hypothesis was accepted because the value of 0.000 <0.05. was rejected and accepted that the increase in students' mathematics learning outcomes using the Student Worksheet (LKPD) Mathematics with a Scientific Approach was better than students who learned through ordinary learning and it can be concluded that the learning media developed was effective to use.